Influence of fuel quality and storage conditions on oxygen consumption in two different wood chip assortments – Determination of the storage-stable moisture content. (1st February 2022) - Hofmann, Nicolas; Borchert, Herbert
Highlights: The dry matter loss of wood chips stored in closed containers can be calculated precisely based on oxygen consumption. Moisture content has the greatest impact on dry matter loss. Temperature, storage duration before drying and chip assortment also significantly affect dry matter loss. No absolute storage-stable moisture content does exist for wood chips. The target moisture content for technical drying depends on the dry matter loss that practitioners are willing to accept. Abstract: Technical drying of wood chips by active ventilation is often applied, i. a. to reduce dry matter and energy losses due to decomposition during storage. However, wood chips are often dried to very low moisture contents (MC) of below 10–15 % (moisture mass fraction on wet basis), that might lead to a waste of drying energy. But the storage-stable MC has not been investigated intensively yet. Therefore, the purpose of our study was to determine as accurately as possible the threshold of MC where significant decomposition starts. Outdoor-stored spruce wood chips were conditioned to different MC and filled into air-tight containers. The oxygen concentration inside the containers was measured after 48 h and the dry matter loss was stoichiometrically calculated. Two different assortments (high/low quality), two storage temperatures (cold/warm) and varying storage durations before sampling were examined. The results showed that MC and oxygen consumption were significantly positively correlated for both assortments and storage temperatures. Even very low MC caused a slight decrease in oxygen concentration. A multiple linear regression model had a high predictive accuracy. For example, during a storage period of 6 months a dry matter loss of 1.1 % would be caused by a moisture content of 20 % for the low-quality assortment at a storage temperature of 21 °C. In conclusion, this study shows that there is no absolute storage-stable MC for wood chips. The point of storage-stability rather depends on the definition of the acceptable dry matter loss. However, the results indicate, that it might not be efficient to dry wood chips below approximately 20 % MC.